Microstructure assessment of bi-modal microcellular polymeric composites developed using multi-stage depressurisation technique in solid-state foaming technology. (21st May 2019) - Gandhi, Abhishek; Panda, Rajesh; Mohanty, Smita; Nayak, S.K.
In this study, bimodal microcellular acrylonitrile butadiene styrene (ABS) foams have been manufactured through solid-state batch foaming process using two staged gas depressurisation technique. After blowing agent saturation, the thermodynamic instability induction on polymer/gas system due to instantaneous pressure drop was performed at two distinct depressurisation stages. Each stage corresponded to nucleation of discrete cell morphology in the polymer matrix. This paper puts forward a study to understand the fundamental mechanism behind bi-modal cell nucleation phenomenon. Further, Influence of holding time, holding pressure, foaming temperature and foaming time on the foam morphological attributes were studied. By altering the process parameters, the morphological attributes in the final product could be controlled efficiently.